New Biomolecules and Drug Delivery Systems as Alternatives to Conventional Antibiotics - Felgueiras, Helena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
New approaches to deal with the growing concern associated with antibiotic-resistant bacteria are in great demand. For many years, antibiotics have widely been employed to treat infections. However, their excessive consumption and misuse have accelerated the rise of antibiotic-resistant microorganisms, which constitute a major challenge to global health. The antibiotic crisis is now a general concern; therefore, alternative biomolecules or drug delivery systems to treat infections are urgently needed. From natural extracts to traditional medicine remedies, to newly engineered nanocapsules and nanoparticles, to bio-based, biodegradable delivery platforms, many systems to fight infections are explored in this book.